A richer and more diverse future for microglia phenotypes. Issue 4 (April 2023) - Wang, Jie; He, Wenbin; Zhang, Junlong
Abstract: Microglia are the only resident innate immune cells derived from the mesoderm in the nerve tissue. They play a role in the development and maturation of the central nervous system (CNS). Microglia mediate the repair of CNS injury and participate in endogenous immune response induced by various diseases by exerting neuroprotective or neurotoxic effects. Traditionally, microglia are considered to be in a resting state, the M0 type, under physiological conditions. In this state, they perform immune surveillance by constantly monitoring pathological responses in the CNS. In the pathological state, microglia undergo a series of morphological and functional changes from the M0 state and eventually polarize into classically activated microglia (M1) and alternatively activated microglia (M2). M1 microglia release inflammatory factors and toxic substances to inhibit pathogens, while M2 microglia exert neuroprotective effects by promoting nerve repair and regeneration. However, in recent years, the view regarding M1/M2 polarization of microglia has gradually changed. According to some researchers, the phenomenon of microglia polarization is not yet confirmed. The M1/M2 polarization term is used for a simplified description of its phenotype and function. Other researchers believe that the microglia polarization process is rich and diverse, and consequently, the classification method of M1/M2 has limitations. This conflict hinders the academic community from establishing more meaningful microglia polarization pathways and terms, and therefore, a careful revision of the concept of microglia polarization is required. The present article briefly reviews the current consensus and controversy regarding microglial polarization typing to provide supporting materials for a more objective understanding of the functional phenotype of microglia. Highlights: Microglia polarization towards M1/M2 type. The idea that microglia polarize into two M1/M2 phenotypes is questioned. Several possible subtypes of microglia.